Rural resettlement scheme evaluation: a case study of the Mfengu in Tsitsikamma - Fakudze, Churchill M (Rhodes University, Faculty of Humanities, Department of Sociology, 2001)
In 1997 South Africa came out with a policy aimed at addressing the legacy of apartheid in respect of an unequal division of land in the country. About 3.5 million people were moved from rural and urban areas between 1960 and 1980 and deposited in the reserves or areas designed for the exclusive occupation of black people. The new land policy attempts to deal with the resultant problems. The policy advocates a three-pronged approach to land reform encompassing (i) land restitution, (ii) land redistribution and (iii) land tenure reform. A number of projects have been carried out under these three aspects. This study aims to investigate and evaluate the results of a completed land restitution case. The Mfengu of Tsitsikamma was chosen as a case study because the people have moved back and are now living on their land. The Mfengu were dispossessed of their land in 1977 by the apartheid government and their land was returned in 1994. Although this case was processed outside of the land restitution legislation (Restitution of Land Rights Act, 22 of 1994), all restitution cases where people return to their original land have to deal with the problems of resettlement. From its involvement in various involuntary resettlement projects, the World Bank concluded that the new communities of resettlers should be designed as a viable settlement system equipped with infrastructure and services and integrated in the regional socio-economic context. The host communities receiving the resettlers should be assisted to overcome possible adverse social and environmental effects from the increased population density. These concerns are valid for the South African situation, and the question is, whether this resettlement encapsulates the above. The goals of the research are twofold. To evaluate the efficiency and effectiveness of the resettlement project and its sustainability. In particular focussing on the constraints to the implementation of the land policy. Research questions include the following: How was the project carried out? Is the resettlement integrated into the socio-economic and development planning of the area? How viable and sustainable is the new settlement? What are the major problems and challenges facing this area and how can they be overcome?
Keywords: Land settlement; Land settlement -- South Africa -- Tsitsikamma; Land settlement -- Developing countries; Land settlement -- South Africa